Inflations and its uncertainty in some ECOWAS member states: Transfer entropy approach - Eric I. Otoakhia (CBN Journal of Applied Statistics, 2021)
This study examines the information flow between inflation and inflation uncertainty (IU) and intrastate inflationary trend among some ECOWAS member states. IU is measured using GARCH models and stochastic volatility model (SV). Transfer en- tropy was adopted to quantify the extent of information flow. The result showed in- formation flow exists from inflation to the GARCH measure of IU. On the reverse flow from inflation uncertainty to inflation, there is no information flow except for Burkina Faso and Gambia which have asymmetric bidirectional flow between inflation and IU. Adopting SV measure for IU, there are no support for causality from inflation to IU for all the member states except Burkina Faso and Cabo Verde. For the re- verse flow, causality exists in all the member states. On the pairwise inflation trend of member states, inflation trends are interconnected and that shocks in one country may transmit to others except for Gambia, Cote d'Ivoire and Burkina Faso. Specifi- cally, Guinea, Liberia and Nigeria inflation shocks have the greatest effect on other WAMZ members within the study period, whereas inflation trend in Benin, Niger and Cote d'Ivoire are the most influential among WAEMU states. In conclusion, inflation - IU relationship is sensitive to how IU is measured leading to mixed findings. This study recommends the need for price stability among the ECOWAS member states. Given the interdependence among some members of each bloc of ECOWAS, policy synchronization on price stability could enhance the overall objective of single digit inflation and reduce the welfare effect of inflation uncertainty
Keywords: C14; D80; E31; 330; ECOWAS; GARCH; inflation-uncertainty; information flow; stochasticvolatility; transfer entropy